2011
DOI: 10.1007/s00114-011-0860-6
|View full text |Cite
|
Sign up to set email alerts
|

Reversed sex change by widowed males in polygynous and protogynous fishes: female removal experiments in the field

Abstract: Sex change, either protogyny (female to male) or protandry (male to female), is well known among fishes, but evidence of bidirectional sex change or reversed sex change in natural populations is still very limited. This is the first report on female removal experiments for polygnous and protogynous fish species to induce reversed sex change in the widowed males in the field. We removed all of the females and juveniles from the territories of dominant males in the cleaner wrasse Labroides dimidiatus (Labridae) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Field evidence for bidirectional hermaphroditism is limited to 10 species in 5 families [Manabe et al, 2013;Kuwamura et al, 2015], and most reports are for species formerly thought to be protogynous. For example, in some socially polygamous and primarily protogynous species where social structure is highly unstable, sexchanged males may revert back to female should they find themselves competing with a larger male (e.g., Okinawa pygmy goby, Trimma okinawae, Manabe et al [2007]; cleaner wrasse, Labroides dimidiatus, Kuwamura et al [2011]). Natural bidirectional sex change has not been reported for any otherwise protandrous species.…”
Section: Bidirectional Sex Changementioning
confidence: 99%
“…Field evidence for bidirectional hermaphroditism is limited to 10 species in 5 families [Manabe et al, 2013;Kuwamura et al, 2015], and most reports are for species formerly thought to be protogynous. For example, in some socially polygamous and primarily protogynous species where social structure is highly unstable, sexchanged males may revert back to female should they find themselves competing with a larger male (e.g., Okinawa pygmy goby, Trimma okinawae, Manabe et al [2007]; cleaner wrasse, Labroides dimidiatus, Kuwamura et al [2011]). Natural bidirectional sex change has not been reported for any otherwise protandrous species.…”
Section: Bidirectional Sex Changementioning
confidence: 99%
“…The widowed males were expected to choose nearby individuals for new mates to avoid the cost of farther movement; reducing movement costs has been suggested as an important factor for the evolution of bidirectional sex change920. The results of this study also suggest that male-male competition for females affects mate choice.…”
Section: Discussionmentioning
confidence: 63%
“…These results support two of the above predictions (P2 and P4). It was also suggested that the widowed males tended to choose the nearby male20, as is predicted in P3, but it has not been confirmed whether a widowed male would choose to pair with another widowed male even in the presence of females, since we removed all females in the previous study.…”
mentioning
confidence: 95%
See 2 more Smart Citations